Toward an efficient determination of tissue-free water tritium in food - Ren, Hong; Ma, Xiaoxiang; Zhou, Lei; Wang, Peng; Chen, Ting; Zou, Xiao; Zou, Hua; Yu, Shunfei; Cao, Yi; Lai, Zhongjun; Lou, Xiaoming; Cao, Yiyao (Frontiers in Public Health, 2023)
Introduction Tritium in the environment constitutes a radiologic concern because it can become part of the hydrogen pool in environmental and biological reservoirs and thereby expose people to low radiation doses. Methods Tissue-free water tritium (TFWT) analysis in food is an important subject of environmental radiation monitoring which plays an important role in the estimation of health risks from environmental tritium exposure. At present, tritium content in food is generally determined by liquid scintillation counter (LSC). To improve the efficiency of tritium analysis by the LSC, we developed a novel method to pretreat TFWT in food using microporous membranes. Results It was determined that the 0.22 μm microporous membrane pretreatment device developed in this study has the following characteristics: it has a wide range of application and can process TFWT samples with conductivity below 5 μS/cm. Sample consumption for the microporous membrane pretreatment device is approximately 5%. The average treatment time is only five minutes, 93% less compared with the current commonly used atmospheric distillation pretreatment method. The results of the comparison and spike experiment show that the samples prepared by microporous membrane pretreatment and atmospheric distillation give satisfactory tritium measurement results for low tritium concentrations of TFWT and high tritium concentration standard samples. The results were statistically analyzed, and there was no significant difference between the results of microporous membrane and atmospheric distillation spike. Discussion Moreover, the method is simple to operate, efficient, and environmentally friendly, and effectively improves the analysis efficiency of TFWT in food.